Pelatihan Pembuatan Surat Rekomendasi Menggunakan Google Forms Pada Dinas BANKESBANGPOL Lombok Tengah - Suherman Apriadi; Ahmad Tantoni (Jurnal Insan Pengabdian Indonesia, 2023)
At this time the role of technology and computers is very important and takes a role that really helps humans in communicating between people, especially in making letters which still use manual letters, especially at my place of field work training (PKL) at the office of the National Unity Agency and Politics ( BANKESBANGPOL), then technological progress plays an important role and takes over all human activities that previously required a long time can be trimmed by this Google form technology, because this Google form does not recognize distance, time and place, so all reports can be done at any time without limitations that make people not bother having to go there to fill in data